Roles and functions of enrolled nurses in Australia: Perspectives of enrolled nurses and registered nurses. Issue 5 (25th March 2018) - Endacott, Ruth; O'Connor, Margaret; Williams, Allison; Wood, Pamela; McKenna, Lisa; Griffiths, Debra; Moss, Cheryle; Della, Phillip; Cross, Wendy
Abstract : Aims and objectives: To determine, from the perspectives of enrolled nurses and registered nurses, the current scope of enrolled nurse practice and to identify the activities that most enrolled nurses frequently performed in their workplace. Background: Enrolled nurse scope of practice in Australia has evolved and expanded over the past decade. However, the unclear role, function and competency differentiation between enrolled nurse and registered nurse leads to role confusion and ongoing professional debate. Design: Exploratory Descriptive Study. Methods: A cross‐sectional online survey of enrolled nurses and registered nurses across Australia was conducted examining their levels of agreement on statements related to the scope of practice and the clinical and nonclinical activities that enrolled nurses were required to perform in their workplace. Results: Valid responses were received from 892 enrolled nurses and 1, 198 registered nurses. Enrolled nurses mostly agreed that they understood their scope of practice; did not undertake roles for which they were unprepared; sometimes undertook activities other than direct patient care; and believed that they operated equally to many registered nurses. The majority of enrolled nurses reported that they performed tasks mostly related to basic patient care in their workplace. There were a number of significant differences between perspectives of registered nurses and enrolled nurses. Conclusions: Clarifying the roles and scope of practice between the registered nurse and the enrolled nurse is important, and explicit differences in responsibility and accountability between their roles must be clearly articulated to harmonise perceptions about role and capability. Health service providers, policymakers and education providers need to work collaboratively to ensure that facets of enrolled nurse education and scope of practice in line with regulation are affirmed by all concerned. Relevance to clinical practice: Health service providers, policymakers and education providers need to work collaboratively to ensure that facets of enrolled nurse education and scope of practice in line with regulation are affirmed by all concerned.